The role of Mab as a source for the mu ring of Uranus (Research Note) - Sfair, R. [UNESP]; Giuliatti Winter, S. M. [UNESP] (Edp Sciences S A, 2012)
Context. We previously analysed how the solar radiation force combined with the planetary oblateness changes the orbital evolution of a sample of dust particles located at the secondary ring system of Uranus. Both effects combined with the gravitational perturbations of the close satellites lead to the depletion of these dust particles through collisions on the surfaces of these satellites on a timescale of hundreds of years.Aims. In this work we investigate if the impacts of interplanetary dust particles (IDPs) onto Mab's surface can produce sufficient particles to replenish the mu ring population.Methods. We first analysed through numerical simulations the evolution of a sample of particles ejected from the surface of Mab and computed the lifetime of the grains when the effects of the solar radiation pressure and the planetary oblateness are taken into account. Then we estimated the mass production rate due to the impacts of IDPs following a previously established algorithm, and used this value to determine the time necessary to accumulate an amount of particles comparable with the mass of the mu ring.Results. Based on an estimate of the flux of interplanetary particles and on the surface properties of Mab it is expected that the satellite supplies material to the ring at a rate of similar to 3 g/s. Meanwhile, our numerical model showed that the ejected particles are removed from the system through collisions with the satellite, and the mean lifetime of the grains may vary from 320 to 1500 years, depending on the radius of the particle.Conclusions. The time necessary to accumulate the mass of the mu ring via ejection from Mab is much shorter than the mean lifetime of the particles, and a stationary regime is not reached. If the ring is kept in a steady state, other effects such as the electromagnetic force and/or the existence of additional bodies may play a significant role in the dust balance, but the current lack of information about the environment renders modelling these effects unfeasible.
Keywords: planets and satellites: rings; methods: numerical; planets and satellites: individual: Uranus